Nondestructive techniques for the assessment and preservation of historic structures - Gonçalves, Luisa M. S.; Rodrigues, Hugo; Gaspar, Florindo (CRC Press, Taylor & Francis Group, 2018)
New technologies play an increasingly important role in the analysis, monitoring, restoration, and preservation of historic structures. This book will present the latest nondestructive technologies used in the characterization, preservation, and structural health monitoring of historic buildings. It will include numerous case studies, as well as theoretical explanations about each of the methods and technologies used in each.